Airway reflux. Issue 1 (16th June 2016) - Johnston, Nikki; Ondrey, Frank; Rosen, Rachel; Hurley, Bryan P.; Gould, Jon; Allen, Jacquie; DelGaudio, John; Altman, Kenneth W.
Abstract : An ever‐increasing number of adult and pediatric disorders have been shown to be influenced or caused by airway reflux. This has become a controversial and complicated aspect of medicine that requires a multidisciplinary approach. Evidence indicates that it is not only the acidic components of gastric refluxate that injure extraesophageal tissues but also the nonacidic components, such as pepsin and bile. There is a realization that proton pump inhibitors will not be effective when nonacidic components of refluxate are causing the problem. New in vitro and in vivo models for the study of airway reflux and new therapeutic and surgical approaches are discussed in this review article.